342 Are lower limb isometric muscle torque and dorsiflexion range of motion associated with calf and achilles tendon injuries among runners? A prospective study. (3rd March 2020) - Dillon, Sarah; Whyte, Enda; Burke, Aoife; O'Connor, Siobhán; Gore, Shane; Moran, Kieran
Abstract : Background: The increasing popularity of running necessitates the investigation of causative factors for injury. Notably, the incidence of Achilles tendon and calf injuries is particularly high. Among the proposed risk factors are lower limb strength deficits and reduced ankle dorsiflexion range of motion (ROM). However, scarcity of prospective research and conflicting findings limits the ability to draw definitive conclusions. Objective: To prospectively investigate the association between isometric muscle torque, dorsiflexion ROM and calf and Achilles injuries among runners. Design: Prospective cohort study. Setting: A study of recreational novice runners in Ireland. Participants : Three hundred and fifteen injury-free recreational runners between 18–65 years were recruited. At the one year follow-up, 21 runners (17 males, 4 females, 42.5±7.4 years) had sustained Achilles or calf injuries. Injured participants were compared to uninjured age and gender matched controls (17 males, 4 females, 42.1±6.8 years). Assessment of risk factors: Baseline assessment consisted of measurement of maximum hip abduction and extension, knee flexion and extension and ankle plantar flexion isometric torque (Nm/kg), using a hand-held dynamometer. Dorsiflexion ROM (degrees) was measured with the knee to wall test using a clinometer. Main outcome measurements: Isometric muscle torque and dorsiflexion ROM were used as independent variables. Achilles and calf injury status one year post-baseline was used as the dependent variable. Independent sample T-tests were used to compare group means. Linear regression was used to evaluate predictive value of these measures (P<0.05). Results: No significant differences existed between groups for any independent variable (P>0.05). The model containing muscle torque and dorsiflexion ROM as predictors did not significantly predict calf and Achilles tendon injuries (R 2 =0.105, F(6, 35)=0.686, P=0.662). No individual predictor was significant (P>0.05). Conclusions: Dorsiflexion ROM and isometric muscle torque did not predict future calf or Achilles injury among recreational runners. These results suggest that these measures may not be appropriate for injury prediction protocols in this population.